2002
DOI: 10.1046/j.1439-0272.2002.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sperm functions in infertile patients with varicoceles

Abstract: Acrosin activity, acrosome reaction and nuclear chromatin condensation were studied in 24 infertile patients with varicoceles and 26 fertile men with or without varicocele. Chromatin condensation, assessed by aniline blue staining, and acrosin activity, evaluated by gelatinolysis technique, were significantly affected in the group of infertile patients. Defective chromatin condensation and defective acrosin activity were detected in 67% and 50% of the infertile patients, respectively. No significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In six of the seven studies, men with varicocele (and no prior infertility) were found to have higher levels of sperm DNA damage than controls (fertile men or sperm donors without varicocele) (23,24,58,(67)(68)(69)(70). In two of the studies, the presence of varicocele was specifically associated with oxidative sperm DNA damage (e.g., high levels of 8-hydroxy-2-deoxyguanosine) (59,68), suggesting that varicocele impairs spermatogenesis and induces sperm DNA damage as a result of increased oxidative stress.…”
Section: Discussion: Are Varicoceles Associated With Increased Dna Frmentioning
confidence: 99%
“…In six of the seven studies, men with varicocele (and no prior infertility) were found to have higher levels of sperm DNA damage than controls (fertile men or sperm donors without varicocele) (23,24,58,(67)(68)(69)(70). In two of the studies, the presence of varicocele was specifically associated with oxidative sperm DNA damage (e.g., high levels of 8-hydroxy-2-deoxyguanosine) (59,68), suggesting that varicocele impairs spermatogenesis and induces sperm DNA damage as a result of increased oxidative stress.…”
Section: Discussion: Are Varicoceles Associated With Increased Dna Frmentioning
confidence: 99%
“…Foresta et al (16) reported that infertile men possess a high percentage of stained spermatozoa with aniline blue versus controls. El-Segini et al (17) and Saleh et al (18) showed that infertile men with varicocele had significantly more spermatozoa with impaired chromatin condensation than fertile donors, indicating a major spermiogenic insult at the spermatid level. Fuse et al (19) reported significant increase of altered sperm chromatin structure and DNA damage in infertile men with varicocele compared with infertile men without varicocele or even fertile subjects.…”
Section: Discussionmentioning
confidence: 99%
“…, 2006). This indicates that one of the spermiogenic insults affecting fertility in varicocele patients takes place at the spermatid level (El‐Segini et al. , 2002) and improved normal protamine content may in turn decrease the chance of DNA damage or fragmentation following varicocelectomy (Nasr‐Esfahani et al.…”
Section: Discussionmentioning
confidence: 99%
“…DNA integrity depends on nuclear remodelling and condensation which is associated with replacement of nuclear histones by transition proteins and then by protamines which take place in spermiogenesis (Mills & Means, 1977;Balhorn, 1982). Infertile patients with varicocele have significantly more spermatozoa with impaired chromatin condensation than both fertile normal donors and fertile subjects with varicocele (El-Segini et al, 2002). Chromomycin A3 (CMA3) has also been used to assess chromatin condensation (Sakkas et al, 1996).…”
Section: Introductionmentioning
confidence: 99%